Green Honey Deli Water Apple (Syzygium aqueum (Burm. f.) Alston “Madu Deli Hijau”): Evaluation of Antioxidant Activities and Phytochemical Content - Hartati, Rika; Widodo, Yasmine; Tarigan, Chrisanta; Fidrianny, Irda (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND OF THE STUDY: Antioxidants are able to fight against free radicals which then prevent degenerative diseases. Antioxidants can be found in many plants such as water apples. AIM OF THE STUDY: This research is aimed to determine the antioxidant activity of green honey deli water apple (Syzygium aqueum) leaves, branches, fruits extracts through 2,2-diphenyl-1-picrylhydrazyl (DPPH) and Cupric Reducing Antioxidant Capacity (CUPRAC) methods, total phenolic content (TPC), total flavonoid content (TFC), correlation of TPC and TFC on antioxidant activity, correlation between DPPH and CUPRAC methods, and content of flavonoid compounds found in ethanol fruit extract of green honey deli water apple. METHODOLOGY: Antioxidant activities were examined by determining ascorbic acid equivalent (AAE) through DPPH and CUPRAC methods. TPC and TFC were determined using UV-vis spectrophotometry. Correlation of TPC and TFC on antioxidant activity and correlation between DPPH and CUPRAC results were analyzed by Pearson’s method. Contents of flavonoid compounds were determined using HPLC. RESULTS: Antioxidant activities of green honey deli water apple leaves, branches, and fruits extracts according to DPPH and CUPRAC methods were 3.97–354.96 mg AAE/g; 10.46–222.51 mg AAE/g respectively. Ethanol leaves extract had the highest TPC (68.14 ± 1.69 g GAE/100 g) and ethyl acetate leaves extract showed the highest TFC (18.65 ± g QE/100 g). TPC and TFC were found to correlate with the antioxidant activities. DPPH and CUPRAC results also correlated significantly positive. CONCLUSION: Phenolic and flavonoid compounds had great contribution on antioxidant activities by DPPH and CUPRAC. The two methods exposed linear results. Ethanol fruits extract of green honey deli water apple contained quercetin (0.16%) and kaempferol (0.39%).